The 18F-PSMA-1007 PET/CT performance on metastasis status and therapy assessment in oligo-metastasis prostate cancer - Wang, Zhuonan; Zheng, Anqi; Li, Yunxuan; Gao, Jungang; Dong, Weixuan; Li, Yan; Duan, Xiaoyi (Frontiers in Oncology, 2022)
Objective: The prostate-specific membrane antigen (PSMA) PET/CT is potentially identifying patients with oligo-metastasis who would be deemed to only have localized disease in the traditional approaches. However, the best selected oligo-metastasis prostate cancer (PCa) patients most likely to benefit from system androgen deprivation therapy (ADT) are still unknown. The aim of this study was to explore the potential 18F-PSMA PET/CT parameters and clinicopathologic characteristics for oligo-metastasis PCa discrimination and follow-up evaluation. Materials and Methods: A total of 180 retrospective patients with different metastasis burdens (PCa of none-metastases, oligo-metastases, and poly-metastases), different metastasis status (untreated and recurrent oligo-metastases), and follow-up ADT were included respectively. A one-way analysis of variance was used to evaluate whether PET/CT parameters and clinicopathologic characteristics were different and univariate/multivariate logistic regression models were applied to assess independent predictors in the metastasis burdens group (89/180). Selected predictors were further compared between different metastasis statuses to test the diagnostic accuracy (69/180). The predictor efficiency was evaluated by the ROC and the cut-off value was used to test the ADT response-to-treatment with a longitudinal cohort (22/180) from untreated baseline to 3-15 months. Results: The significant group differences were observed on SUVmax (P = 0.012), International Society of Urologic Pathologists (ISUP, P＜0.001) and Gleason Score (P＜0.001). Poly-Metastases patients had higher SUVmax, ISUP and Gleason Score compared to Non-Metastases and Oligo-Metastases patients, respectively (P＜0.05, all), and no difference between Non-Metastases and Oligo-Metastases. The SUVmax, ISUP and Gleason Score were independent predictors for metastasis burdens discrimination. The untreated and recurrent oligo-metastases lesions SUVmax were also different (P = 0.036). The AUC of ROC for oligo-metastasis prediction was 0.658 (P = 0.039) when the primary prostatic carcinoma focus SUVmax was higher than 28.22, ADT response-to-treatment patients (5/5 in 22) were all progress in a follow-up test. Conclusion: The SUVmax can discriminate PCa metastasis degree and oligo-metastasis status. The ADT-treated oligo-metastasis patient may still have disease progression when the primary prostatic carcinoma focus SUVmax is greater than 28.22.